Evaluation of the Expression Levels of Circulating microRNA-204-5p and Related to Some Biochemical Parameters in Patients with Hypertension - Al-Deresawi, Mahdi Saber; Al-Rekaabi, Aseel Razak (Journal of Science in Medicine and Life, 2025)
Hypertension is a multifactorial disorder influenced by complex genetic and epigenetic interactions. This study designed to evaluate the microRNA-204-5p gene expression in serum of hypertension patients and its relationship to some clinicopathological features. This include (100 patients with Hypertension and 50 individuals as control group apparently healthy). All subjects aged 45-60 years. Quantitive Real-Time PCR results showed the levels of microRNA-204-5p gene was high significant increased in hypertension patients compared to healthy group. Depending to Body Mass Index the expression of microRNA-204-5p showed significantly increased in both obese and overweigh hypertension patients. In other hand; there’s no significant difference in microRNA-204-5p levels between age and sex with miR-204 (P=0. 591 and 0.490 for age and sex, respectively). In conclusion, the miR-204 may be involved in blood pressure regulation in both patients and healthy individuals and the levels of miR-204 are rising in female patients, as well as in patients with hypertension who are overweight or obese.